Do technology-based devices improve carious lesion detection? - Vitor, Luciana Lourenço Ribeiro; Kobayashi, Tatiana Yuriko; Carrara, Cleide Felicio Carvalho; Rios, Daniela; Silva, Thiago Cruvinel; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini (Brazilian Dental Science, 2016)
Objective:  To compare the visual-tactile examination with the technology-based caries detection examinations in children. Methods: We assessed the teeth next to the cleft area of 95 children aged 6 to 12 years with oral clefts but without the presence of any associated syndrome or craniofacial anomaly, according to the following detection methods: visual-tactile examination (Method 1), visual-tactile examination through operating microscope (Method 2), visual examination through LED-based fluorescence device (Method 3), using ICDAS-II scores. The caries detection methods were compared by Friedman test (P